IDENTIFICATION OF THE EFFECTIVENESS OF DENTAL MEASURES FOR THE PREVENTION OF PERIODONTAL DISEASES IN METAL WORK PRODUCTION WORKERS - Musayeva Gulchekhra Abdukhamitovna; Khotamova Madinakhon Anvarovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
In the process of intensive industrial development, the study of the role of harmful and health-related factors of the production environment is timely and very important. After all, unfavorable working conditions contribute to the formation of various pathological processes in the human body (Amirov N.H., 2018). Prolonged exposure to a complex of production factors, along with a deterioration in the health of workers, can usually lead to pathological changes in the oral mucosa, periodontal diseases, and hard dental tissues (Galiullin A.N., 2014). Metallurgical production belongs to the industries with the most severe, dangerous and harmful working conditions, which have a direct impact on the functional systems of the body, change homeostasis, neuro-humoral regulation in it and lead to pathological changes in the oral cavity (Novikova R.T., 2016). Harmful conditions in the production of metal structures, despite the availability of occupational health and safety measures, represent extreme conditions for workers and require further development of comprehensive programs for the prevention of major dental diseases.